Pelatihan Universal Design For Learning Sebagai Alat Pengembangan Kurikulum Guru Pjok Di Kecamatan Rangkasbitung Kabupaten Lebak - Widyawan, Dena; Ramdhan Rahman (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2023)
This community service activity took the form of socializing Universal Design for Learning as a Teacher Curriculum Development Tool PJOK in collaboration with Ikatan Guru Olaharaga Nasional (IGORNAS). The training place at the IGORNAS secretariat of Lebak Regency. This training was attended by PJOK teachers in the Rangkasbitung District. As a result of this service, teachers understand the key concept of universal design for learning in which there are goals and characteristics of expert learners and also understand the purpose of using universal design for learning for learning principles, even though PJOK teachers in Rangkasbitung District have just attended training on universal design for their learning quickly grasps the material because universal design for learning is easy to understand and implement in teaching children with disabilities.